Legal Vacuum in Issuance and Revocation of Mining Business Permits - Ojak Situmeang; Herman Bakir (Rechtsnormen: Journal of Law, 2024)
Background: The management of Indonesia's abundant natural resources, particularly through mining activities, is closely tied to the issuance of permits governed by regulations such as the Mineral and Coal Law and its derivative laws. However, challenges like regulatory uncertainty, overlapping authority between central and regional governments, and inconsistent law enforcement create a legal vacuum that hinders the effectiveness of permit issuance and revocation. Objectives: This study aims to analyze the mechanisms for issuing and revoking mining business permits in Indonesia. It also seeks to identify legal challenges and provide recommendations to strengthen the legal framework and ensure effective implementation. Methods: This research employs a normative legal approach, focusing on the analysis of laws, regulations, and case studies related to mining business permits. Secondary data were analyzed qualitatively to evaluate the consistency and effectiveness of the legal framework. Research Findings: The findings reveal that the issuance and revocation processes are plagued by unclear regulations and fragmented governance. These issues result in regulatory inefficiencies and weak law enforcement, impeding sustainable resource management. Conclusion: To address the legal vacuum, reforms are required to ensure clarity, eliminate overlapping authority, and improve law enforcement. Strengthening the legal framework will enhance the management and regulation of mining permits in Indonesia.